Клінічні, ехокардіографічні, лабораторні та прогностичні аспекти хронічної серцевої недостатності з надлишковою масою тіла та ожирінням залежно від сироваткового вмісту адипонектину - Нетяженко, В. З.; Бідзіля, Петро Петрович; Каджарян, Віталій Георгійович; Netyazhenko, V. Z.; Bidzilya, P. P.; Kadjaryan, V. G.; Бидзиля, П. П.; Каджарян, В. Г. (Сумський державний університет, 2018)
Метою дослідження було вивчення особливостей клінічного перебігу хронічної серцевої недостатності (ХСН), структурнофункціональних змін серця, показників ліпідного, вуглеводного, адипоцитокінового обміну та маркерів системного запалення у хворих з надлишковою масою тіла (НМТ) та ожирінням залежно від сироваткового вмісту адипонектину, для оцінки його прогностичної значущості щодо впливу на перебіг захворювання впродовж 5 років. Матеріали і методи дослідження. Загалом було обстежено 84 хворих на ХСН ІІ–ІІІ функціонального класу (ФК) з НМТ та ожирінням І–ІІІ ступеня. Пацієнти були поділені на 2 групи залежно від вмісту адипонектину в сироватці крові. До І групи увійшов 21 досліджуваний, з вмістом адипонектину більше 31,5 (40,4 [37,3; 47,2]) мкг/мл, ІІ групу становили 63 пацієнти з рівнем адипонектину менше 31,5 (12,3 [8,50; 18,7]) мкг/мл. Всі хворі підлягали стандартному клінічному, біохімічному та ехокардіографічному дослідженню, згідно існуючих загальноприйнятих настанов. Вміст адипонектину в сироватці крові визначали імуноферментним методом. Статистичну обробку проводили за допомогою ліцензійного пакету статистичних програм Statistica 6.0. Результати дослідження. Високий вміст адипонектину в сироватці крові хворих на ХСН з НМТ та ожирінням супроводжувалось більшими частотою серцевих скорочень (ЧСС), ФК захворювання, розміром лівого передсердя (ЛПс), товщини задньої стінки лівого шлуночка (ТЗСЛШ), індексу маси міокарда ЛШ1 (ІММЛШ1), ступеня кальцинозу мітрального (МК) та аортального клапанів (АК), ступеня регургітації МК та АК, переважанням поширеності суб’єктивних, об’єктивних симптомів захворювання, частоти ІІІ ФК ХСН, вмісту ІЛ-6, ІЛ-10, ФНП- α, співвідношення адипонектин/резистин, ФНП-α/ІЛ-10, частоти смерті впродовж 5 років та сумарної кумулятивної кінцевої точки. Одночасно були нижчими систолічний артеріальний тиск (САТ), фракція викиду ЛШ, вміст холестерину ліпопротеїнів дуже низької щільності (ХС ЛПДНЩ), тригліцеридів (ТГ) та співвідношення резистин/адипонектин. Отримані дані свідчать, що за високого вмісту адипонектину відбувається важчий перебіг ХСН в умовах НМТ та ожиріння, що проявляється поглибленням порушень клінічних, ехокардіографічних, лабораторних та гуморальних ланок патогенезу захворювання. Today, chronic heart failure (CHF) is one of the main causes of death and disability among patients with cardiovascular disease. Despite the fact that significant progress has been made in the treatment and diagnosis of CHF, mortality rates remain high. The possible explanation for this is the increase in the age of the human population and the involvement of other mechanisms that have not yet been investigated to the pathogenesis of the disease. Recently, more and more attention of researchers is devoted to the study of the components of the exchange of adipocytokines, biologically active substances, which produced by visceral fatty tissue. One of the most interesting representatives of adipocytokines is adiponectin, which has a number of metabolic and pleiotropic effects. Scientists have proven a significant role in the pathogenesis of diabetes mellitus, lipid metabolism disorders, obesity and cardiovascular pathology. There are a number of studies that examined the effects of adiponectin on the development, course, and results of CHF. Disseminating thoughts of researchers regarding changes in the level of adiponectin in CHF conditions, some of them have shown hypoadiponectinemia, but more and more works have recently shown an increase in adiponectin content and its negative prognostic effect. The World Health Organization has reported obesity as a non-infection epidemic. The abdominal type of obesity and overweight remain one of the main predictors of the onset and progression of many diseases, and CHF in particular. However, recently, more and more works show the better course and results of disease in patients with moderate obesity. This was called as "obesity paradox". Taking into account the foregoing, the study of the effect of adiponectin content in serum on various pathogenetic components of CHF in patients with overweight and obesity is relevant and timely, in order to further develop prognostic criteria and therapeutic effects. Purpose: to investigate clinical course of CHF, structural and functional changes in the heart, lipid, carbohydrate, adipocytokines metabolism and markers of systemic inflammation in patients with overweight and obesity depending on the serum content of adiponectin, to assess its prognostic effects on the five-year course of the disease. Materials and methods. Totally 84 patients with CHF II–III functional class (FC) with overweight and obesity I–III degree were examined. Patients were divided into 2 groups depending on adiponectin content in blood serum. To the І group entered 21 investigated, with adiponectin content higher than 31,5 (40,4 [37,3; 47,2]) mcg/ml, the ІІ group was presented by 63 patients with the level of adiponectin lower than 31,5 (12,3 [8,50; 18,7]) mcg/ml. All patients were subject standard clinical, biochemical and to echocardiographic research, in obedience to the existent generally accepted guidelines. Content of adiponectin in serum of blood were measured by ELISA method. Statistical analysis were conducted by means of the licensed package of statistical software’s (Statistica 6.0) Results. The high content of adiponectin in blood serum of patients with CHF with overweight and obesity was accompanied by higher heart rate, FC of disease, left atrium size, left ventricle posterior wall diameter, left ventricle myocardial mass index1, degree of calcinosis mitral and aortal valve, degree of regurgitation of mitral and tricuspid valve, increasing prevalence of subjective, objective symptoms of the disease, frequency CHF III FC, the content of IL-6, IL-10, TNF-α, the ratios of adiponectin/resistin, TNF-α / IL-10, the incidence of five-year mortality and total cumulative endpoint. At the same time, there were lower systolic blood pressure, left ventricle ejection fraction, very low-density cholesterol and triglycerides contents and resistin/adiponectin ratio. The obtained data indicate that the high content of adiponectin results in a heavier course of CHF in the conditions of overweight and obesity, which is manifested by the deepening of violations of clinical, echocardiographic, laboratory and humoral links pathogenesis of the disease. Conclusion. The high content of adiponectin in serum of blood in patients with overweight and obesity characterized by a severe course of CHF and has a negative prognostic influence on the results of the disease for five years. Целью исследования было изучение особенностей клинического течения хронической сердечной недостаточности (ХСН), структурно-функциональных изменений сердца, показателей липидного, углеводного, адипоцитокинового обмена и маркеров системного воспаления у больных с избыточной массой тела (ИМТ) и ожирением в зависимости от сывороточного содержания адипонектина, для оценки его прогностического влияния на пятилетнее течение заболевания. Материалы и методы исследования. Всего было обследовано 84 больных ХСН II-III функционального класса (ФК) с ИМТ и ожирением I-III степени. Пациенты были разделены на 2 группы в зависимости от содержания адипонектина в сыворотке крови. В І группу вошел 21 исследуемый, с содержанием адипонектина больше 31,5 (40,4 [37,3; 47,2]) мкг/мл, ІІ группу составили 63 пациента с уровнем адипонектина меньше 31,5 (12,3 [8,50; 18,7]) мкг/мл. Все больные подлежали стандартному клиническому, биохимическому и эхокардиографическому обследованию, согласно существующим общепринятым руководствам. Содержание адипонектина в сыворотке крови определяли иммуноферментным методом. Статистическую обработку проводили с помощью лицензионного пакета статистических программ Statistica 6.0. Результаты исследования. Высокое содержание адипонектина в сыворотке крови больных ХСН с ИМТ и ожирением сопровождалось большими частотой сердечных сокращений, ФК заболевания, размером левого предсердия, толщины задней стенки левого желу дочка (ЛЖ), индекса массы миокарда ЛЖ1, степени кальциноза митрального (МК) и аортального клапанов (АК), степени регургитации МК и АК, преобладанием распространенности субъективных, объективных симптомов заболевания, частоты ІІІ ФК ХСН, содержания ИЛ-6, ИЛ-10, ФНО-α, соотношение адипонектин/резистин, ФНО-α/ИЛ-10 частоты смерти в течении 5 лет и суммарной кумулятивной конечной точки. Одновременно были ниже систолическое артериальное давление, фракция выброса ЛЖ, содержание холестерина липопротеинов очень низкой плотности, триглицеридов и соотношение резистин/адипонектин. Полученные данные свидетельствуют, что при высоком содержании адипонектина имеет место более тяжелое течение ХСН в условиях ИМТ и ожирения, которое проявляется углублением нарушений клинических, эхокардиографических, лабораторных и гуморальных звеньев патогенеза заболевания.
Clinical, echocardiographic, laboratory and prognostic aspects of chronic heart failure with overweight and obesity depending on serum adiponectin content
Клинические, эхокардиографические, лабораторные и прогностические аспекты хронической сердечной недостаточности с избыточной массой тела и ожирением в зависимости от сывороточного содержания адипонектина
Keywords: хронічна серцева недостатність; надлишкова вага; ожиріння; адипонектин; сердечная недостаточность; избыточный вес; ожирение; heart failure; overweight; obesity; adiponectin